Meningkatkan Efisiensi dan Efektifitas Kerja Inseminator di Wilayah SPAKU Sapi Potong Dengan Menggunakan Teknologi CIDR - Gunawan Gunawan; Saiful Anwar; Samsul Rizal; Ginta Riady (Jurnal Agripet, 2000)
ABSTRACT. A study on how to improve the efficiency and the effectivity of the Inseminators work in beef cattle SPAKU area has been done. The study was designed as a field experimentation which used 40 prolonged anestrus postpartum cows. Sample cows were divided into two groups which consisted of control group (20 heads) and treatment group (20 heads). The treatmet group were treated with CIDR in order to allow oestrous synchronization at the end of the treatment. The result of the study showed that synchronization protocol allows the inseminator to work according to a preplanned schedule and to inseminate a number of oestrous cows in one working day. Statistical analisys indicated that all cows which were treated with CIDR became pregnant compared with those of control group. It can be said that oestrous synchronization with CIDR had higly significantly increased pregnancy percentage in treatment group (P0,01) compared with those of control group.